2012
DOI: 10.1039/c2cs35181a
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime radical observations and chemistry

Abstract: The nitrate radical, NO(3), is photochemically unstable but is one of the most chemically important species in the nocturnal atmosphere. It is accompanied by the presence of dinitrogen pentoxide, N(2)O(5), with which it is in rapid thermal equilibrium at lower tropospheric temperatures. These two nitrogen oxides participate in numerous atmospheric chemical systems. NO(3) reactions with VOCs and organic sulphur species are important, or in some cases even dominant, oxidation pathways, impacting the budgets of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
428
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 443 publications
(443 citation statements)
references
References 478 publications
(630 reference statements)
11
428
4
Order By: Relevance
“…Moreover, the predominance of the nighttime P NO3+DMS (Fig. 2) during winter, even surpassing the daytime P NO2+OH as the main NO x sink, was found to be in agreement with previous studies (30,33). P NO3+DMS gave rise to the Δ 17 O winter peak in the SSM.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, the predominance of the nighttime P NO3+DMS (Fig. 2) during winter, even surpassing the daytime P NO2+OH as the main NO x sink, was found to be in agreement with previous studies (30,33). P NO3+DMS gave rise to the Δ 17 O winter peak in the SSM.…”
supporting
confidence: 79%
“…Recently, questions have emerged regarding the role of N 2 O 5 in models, especially in the clean marine atmosphere (5,6,29). These studies generally point to an overestimation of the uptake coefficient of N 2 O 5 (30). However, in the present case, sensitivity tests showed that the SSM was unaffected by three orders of magnitude changes in the N 2 O 5 uptake coefficient (range: 10 −3 to 1).…”
mentioning
confidence: 38%
See 1 more Smart Citation
“…Both column-and point measurements of tropospheric NO 3 indicate a strong vertical gradient in its mixing ratio with significantly elevated levels aloft (Aliwell and Jones, 1998;Allan et al, 2002;von Friedeburg et al, 2002;Stutz et al, 2004;Brown et al, 2007a;Brown et al, 2007b;Brown and Stutz, 2012). The NO 3 gradient is the result of lower production rates close to the ground, where O 3 levels are depleted due to deposition and also lower loss rates aloft as the concentration of 5 reactive traces gases from ground level emissions decreases with altitude.…”
Section: Vertical Gradient In No 3 Reactivitymentioning
confidence: 99%
“…OH radicalinduced oxidation taking place mainly during daytime with the NO 3 radical (formed by reaction of O 3 with NO 2 , (R1)) accounting for the major fraction of radical-induced loss of BVOC at nighttime (Wayne et al, 1991;Atkinson, 2000;10 Atkinson and Arey, 2003a, b;Brown and Stutz, 2012;Mogensen et al, 2015;Ng et al, 2016;Liebmann et al, 2017). The rapid photolysis of NO 3 by sunlight (R5, R6) and reaction with NO (R2) typically reduces its lifetime to a few seconds during day-time.…”
mentioning
confidence: 99%